PENGARUH KANDUNGAN UNSUR HARA LIMBAH CAIR PABRIK GULA TERHADAP SIFAT KIMIA DAN FISIKA TANAH DI LAHAN SAWAH KECAMATAN BULULAWANG KABUPATEN MALANG - Faroni, Fariq; Hadi Pratiwi, Anggraeni; Lukman, Arief (Fakultas Sains dan Teknologi, 2022)
Pabrik Gula Krebet disposes of liquid waste into the nearest river, which can pollute the aquatic and soil environment. However, sugar factory effluent contains nutrients N and P as well as organic matter that is beneficial to plants (within a certain maximum limit). The study aims to determine whether there is an effect of the content of nutrients and organic matter of sugar factory wastewater on the physical and chemical properties of the soil in the paddy fields Bululawang Malang. Parameters of soil properties that were analyzed included pH, CEC, N-Total, P2O5, Potassium, C-Organic, bulk density, soil porosity, and specific gravity, while water parameters included pH, PO4, and Potassium. Based on the results of soil analysis, it is known that the porosity value on the shaft criteria is in the range of 63-72%, pH on the acid criteria with a value of 5.8-6.4, CEC on low to moderate criteria with a value of 5.5-21.2 cmol/kg, organic matter on high criteria with a value of 4.3-6.2%, P2O5 on the high criteria of 52.6-70.0 ppm, bulk density is on the medium criteria of 0.66-0.96 gr/cm3, the total N value on the medium criteria of 0.23-0.28%, and potassium on the moderate criteria of 168.5-256.2 mg K/kg. The results of the water analysis showed that PO4 was within the quality standard limit of 0.51-0.83 me/l, the potassium content was within the water quality standard limit value of 0.25-0.28 me/l, for pH parameters is above the quality standard limit of 5.93-6.23. The coefficient of determination test results showed that the difference in distance from the waste source affected the bulk density, soil porosity, organic matter, pH, CEC, total N, soil potassium. While on pH, PO4 and potassium water had no effect on soil P2O5 parameters. The results of the correlation coefficient test showed that distance differences were positively correlated with porosity, organic matter, CEC, total N, soil potassium, but negatively correlated with bulk density, soil pH and water pH. Keywords:sugar factory liquid waste, nutrients, soil properties